Occupational hazards of traditional healers: repeated unprotected blood exposures risk infectious disease transmission. Issue 11 (16th September 2016) - Audet, Carolyn M.; Salato, José; Blevins, Meridith; Silva, Wilson; González‐Calvo, Lázaro; Vermund, Sten H.; Gaspar, Felisbela
Abstract: Objective: Healers provide support for acute and chronic illnesses in rural Mozambique, such as socially acceptable traditional 'vaccinations' (subcutaneous cuts in the skin to rub herbs directly into the bloody lesion). We aimed to document the frequency of blood exposure by traditional practitioners in Mozambique. Methods: We conducted surveys with a simple random sample of 236 traditional healers in Zambézia province. Chi‐square and Wilcoxon rank‐sum tests were used to compare 'injection' behaviours across districts. Results: Healers treated a median of eight patients in the past month (IQR: 4–15). About 75% conducted 'injections'. These healers 'injected' a median of four patients (IQR: 1–8), used a new razor a median of three times (IQR: 1–8), and almost never used gloves. Lifetime blood exposures among those who provided 'injections' during treatments were estimated to be 1758 over a healer's career. Conclusion: The majority of healers are exposed repeatedly to patient blood. Given the high prevalence of HIV, hepatitis B and C virus, and other blood‐borne agents, specific healer practices are an occupational hazard and reuse of razors is risky for their clients.